Experience of using Community Radio for Fistula Communication in Bangladesh - Biswas, Nitta; Huda, Sk Nazmul (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To share the experience of using community radio networks for female genital fistula communication in Bangladesh. Methods: We selected 11 community radio stations from remote areas in Bangladesh. Four hours orientation training was provided to manager and fistula focal person per radio station. We provided pre-recorded education and advocacy materials for fistula prevention and communication. Station staffs were provided with a manual for fistula communication. Results: 32 key staff members of community radios were trained. At least 33 episodes were broad casted focusing on prevention of early marriage, care of obstructed labor, treatment and rehabilitation of fistula. Information about fistula prevention, case identification, repair center and rehabilitation were provided to an estimated number 660,000 people living in hard to reach places through community radio stations. They incorporated fistula messages song, dramas and talk shows on fistula throughout the year. Conclusions: Community radio is a low cost, effective media for fistula communication in hard to reach areas. It is capable of linking a range of stakeholders and can be a strong force for facilitation of social movement for fistula free communities.